SAT0486 Myeloablation followed by autologous stem cell rescue leads to normalisation of serum il-6 levels in patients with systemic sclerosis. (12th June 2018) - Bellocchi, C.; Sullivan, K.; Goldmuntz, E.; Ying, J.; Keyes-Elstein, L.; Varga, J.; Hinchcliff, M.E.; McSweeney, P.; Furst, D.E.; Nash, R.; Crofford, L.J.; Welch, B.; et al.
Abstract : Background: In the randomised Scleroderma: Cyclophosphamide or Transplantation (SCOT) trial, myeloablation followed by autologous hematopoietic stem cell transplantation (HSCT) led to improved clinical outcomes compared to monthly cyclophosphamide (CYC) treatment in systemic sclerosis (SSc). 1 Moreover, there is emerging evidence on the role of the Th2 cytokine, interleukin 6 (IL-6) in SSc pathogenesis, and clinical trials targeting the IL-6 pathway have been completed. 2 Objectives: To investigate the association of IL-6 with baseline clinical features and to examine its longitudinal changes in the treatment arms of the SCOT trials. Methods: The SCOT trial enrolled 75 subjects with diffuse SSc, 65 (HSCT=31, CYC=34) subjects with a mean disease duration of 2.2 years were analysed; 65 age and gender matched controls were also investigated. All available serum samples at the baseline (n=65), 8- (n=55) and 26- (n=45) month visits were included. IL-6 was determined using ultra-sensitive Simoa assay. For purposes of comparison, prominent, pro-inflammatory Th1 cytokines, Interleukin 1β (IL-1β), interleukin 12 (IL-12), and interferon gamma (IFN-γ) were determined by Rule Based Medicine multiplex assays. The serum IFN-γ levels were in undetectable range in the majority of patient and control samples. Therefore, the comparative analysis focused on IL-1β and IL-12. Results: Serum IL-6 was higher in SSc patients than controls (fold change=1.62, p<0.001). At the baseline visit, IL-6 positively correlated with hsCRP (rs=0.56, p<0.001) and modified Rodnan Skin Score (rs=0.26, p=0.037) and showed an inverse relationship with disease duration (r=−0.26, p=0.037), while it did not have a significant correlation with forced vital capacity (rs=−0.19, p=0.126). Moreover, no significant correlations were observed with IL-1β and IL-12. A comparison of regression lines revealed a significant decrease in serum IL-6 levels in the HSCT arm relative to CYC (p=0.0004). By 26 months, the HSCT arm no longer showed upregulation of serum IL-6 relative to controls while the CYC arm remained upregulated. In contrast, time trends for IL-1β and IL-12 did not differ significantly between arms (p-values=0.161 and 0.456, respectively). (figure 1). Conclusions: The Serum IL-6 levels decreased significantly 26 months after HSCT, while the two Th1, proinflammatory cytokines did not show similar changes. This finding supports the notion that this treatment modality normalises specific serum protein imbalances implicated in SSc pathogenesis. References: [1] Sullivan KM, Goldmuntz EA, Keyes-Elstein L, McSweeney PA, Pinckney A, Welch B, et al. Myeloablative Autologous Stem-Cell Transplantation for Severe Scleroderma. N Engl J Med2018. [2] Khanna D, Denton CP, Jahreis A, van Laar JM, Frech TM, Anderson ME, et al. Safety and efficacy of subcutaneous tocilizumab in adults with systemic sclerosis (faSScinate): a phase 2, randomised, controlled trial. Lancet2016. Disclosure of Interest: None declared